Chemical constituents from fruits of Macaranga denticulata (Euphorbiaceae) (Part 2). Issue 5 (24th October 2018) - Vu, Le Tran Nguyen; Ngan, Truong Bich; Phuong, Le Thi; Huong, Doan Thi Mai; Litaudon, Marc; Van Hung, Nguyen; Thach, Tran Dang; Van Cuong, Pham
Abstract: Macaranga denticulata is a 15‐18 m tall plant with rounded edges and long, rounded bark, 5 mm wide black covered with glands. In traditional medicine, this plant was used to treat fulminant hepatitis, dysentery, and urinary retention. In previous studies, we reported 13 isolated compounds from the fruits of Macaranga denticulata . In this study, we describe the isolation and structural characterizations of seven compounds: 5‐(( E )‐3, 5‐dihydroxystyryl)‐3‐(( E )‐3, 7‐dimethylocta‐2, 6‐dien‐1‐yl)benzen‐1, 2‐diol (1 ), poilaneic acid (2 ), stigmast‐4‐en‐6 β ‐ol‐3‐one (3 ), taraxerol (4 ), rel‐5‐(3S, 8S‐dihydroxy‐1 R, 5 S ‐dimethyl‐7‐oxa‐6‐oxobicyclo[3, 2, 1]‐oct‐8‐yl)3‐methyl, 2 Z, 4 E ‐pentadienoic acid (5 ), ellagic acid 3, 3'‐dimethyl ether‐4‐ O ‐ β‐ D ‐ glucopyranoside (6 ), 3‐hydroxypropanoic acid (7 ). The structures of the isolated compounds were established on the basis of their spectral data, including mass and NMR spectrometry.